2011
DOI: 10.1111/j.1471-4159.2010.07070.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasmalogen synthesis is regulated via alkyl‐dihydroxyacetonephosphate‐synthase by amyloid precursor protein processing and is affected in Alzheimer’s disease

Abstract: J. Neurochem. (2011) 116, 916–925. Abstract Lipids play an important role as risk or protective factors in Alzheimer’s disease, which is characterized by amyloid plaques composed of aggregated amyloid‐beta. Plasmalogens are major brain lipids and controversially discussed to be altered in Alzheimer’s disease (AD) and whether changes in plasmalogens are cause or consequence of AD pathology. Here, we reveal a new physiological function of the amyloid precursor protein (APP) in plasmalogen metabolism. The APP int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 70 publications
2
96
0
Order By: Relevance
“…In line with these findings, it has been recently reported that differentiated PC12 cells, treated with the γ-secretase inhibitor DAPT, show an increase in ganglioside level in neuritic terminals [62], further strengthening that PS proteolytic activity alters ganglioside homeostasis. Additionally, we and others recently found that cleavage products of APP are involved in the regulation of several proteins and that this regulation is disturbed in absence of PS, in mutated PS or in AD [11,30,31,32,63,64,65]. Main focus was attended to the APP intracellular domain (AICD), which is released to the cytosol and discussed to be involved in gene transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line with these findings, it has been recently reported that differentiated PC12 cells, treated with the γ-secretase inhibitor DAPT, show an increase in ganglioside level in neuritic terminals [62], further strengthening that PS proteolytic activity alters ganglioside homeostasis. Additionally, we and others recently found that cleavage products of APP are involved in the regulation of several proteins and that this regulation is disturbed in absence of PS, in mutated PS or in AD [11,30,31,32,63,64,65]. Main focus was attended to the APP intracellular domain (AICD), which is released to the cytosol and discussed to be involved in gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…AICD was found to decrease gene expression of the catalytic subunit of serine-palmitoyl-CoA transferase (SPT) [31] and to down regulate the expression of GD3-synthase (GD3S), the key enzyme converting a- to b- series gangliosides [11]. Furthermore, AICD was reported to increase the expression level of the alkyl-dihydroxyacetone phosphate-synthase (AGPS), a rate limiting enzyme in plasmalogen synthesis [32], representing major brain lipids which are discussed to be altered in AD [66,67]. AICD was also found to suppress the transcription of lipoprotein receptor LRP1 [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the intercellular domain of APP was found to decrease the expression of alkyl-dihydroxyacetonephosphate synthase (AGPS), the rate-limiting enzyme in pPE biosynthesis [50]. In addition to modulating AGPS levels, AD pathogenesis could affect pPE levels in another way.…”
Section: Plasmalogen Ethanolaminesmentioning
confidence: 99%
“…The α-secretase cleaves APP within the Aβ domain, thus precluding the formation of Aβ peptides. The γ-secretase cleavage of βCTF/C99 and αCTF/C83 liberates the APP intracellular domain (AICD), which translocates to the nucleus and regulates gene expression [306][307][308][309][310].…”
Section: Proteolytic Processing Of App Amyloidogenic App Processingmentioning
confidence: 99%